Evaluation of Advantages and Disadvantages of Village Information Systems in Supporting Sustainable Development Programs - Agestya Prabu Marsyadi; Muhammad Ihsan; Zulhipni Reno Saputra (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2025)
In the digital age, information technology has become essential in many areas of life, including public administration. As a public service provider, the government needs to utilize technology to increase efficiency, transparency, and accountability in providing services to its citizens. The concrete expression of the innovation is the development of the Village Information System (SID) which aims to enable the village government to manage population data, development, and village administration in an integrated manner. The Ogan-Ilir Regency Government has developed and implemented two web applications, SIDESI (Integrated Village Information System). This application aims to facilitate the management of municipal data and village administration. SIDESI allows villages to consolidate data relevant to various development needs. This study uses a quantitative approach using a survey method using a questionnaire to evaluate the advantages and disadvantages of the SIDESI web application. This approach aims to obtain data obtained from questionnaires filled out by users directly from the SIDESI web application. The results of the use of the SIDESI application web application are very effective in managing population data, with features that make it easier for village officials to input family and resident data in a systematic and structured manner. This speeds up the data management process at the village level, as well as reduces the risk of human error in data recording.